IPhone fully loaded - Ihnatko, Andy (Office Essentials collection, 2010)
"The new, even more powerful iPhone enables you to carry almost everything you need right in your pocket. iPhone Fully Loaded, 3rd Edition shows you things about your iPhone that you never imagined. Written by Mac superstar and Chicago Sun Times technology columnist Andy Ihnatko, this irreverent and fun guide shows you how to put everything on your iPhone from old LPs, radio/TV shows, and movies to spreadsheets, presentations, and PC rescue files. It also covers all the latest applications as well as the basics like e-mail, music, and of course, making phone calls."--Resource description page.